Aperiodic fiber Bragg gratings written by ultrashort laser pulses using the line-by-line technique - Goebel, Thorsten A.; Bharathan, Gayathri; Richter, Daniel; Krämer, Ria G.; Ams, Martin; Fuerbach, Alex; Nolte, Stefan (Optics InfoBase Conference Papers, 2018)
We demonstrate the successful inscription of aperiodic fiber Bragg gratings (AFBGs) by femtosecond laser pulses using the line-by-line technique. The AFBGs were designed with 10 transmission notches to work as wavelength filter elements in astronomy.
CRIS-Team Scopus Importer:2023-04-20